Aktivitas Antioksidan Ekstrak Metanol Daun Rhizophora apiculata - Ramli, Husnul Khatimah; Aprianti, Eka; Roiska, Riris; Azis, M. Aksa; Putinur, Putinur (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2025)
Mangroves are well-known for their diverse benefits, with all plant parts containing beneficial bioactive compounds. This study aims to evaluate the antioxidant activity of the methanolic extract of Rhizophora apiculata mangrove leaves. Mature mangrove leaves were extracted using 70% methanol through a maceration method, and antioxidant activity was assessed using the DPPH radical scavenging assay. The results indicated that the extract exhibited inhibition percentages ranging from 56% to 91% at concentrations of 50–1000 ppm, with an IC₅₀ value of 30.86 µg/mL. These findings suggest that the methanolic extract of mature R. apiculata leaves possesses powerful antioxidant potential (IC₅₀ < 50 µg/mL).